Nesting range expansion of loggerhead turtles in the Mediterranean: Phenology, spatial distribution, and conservation implications - Hochscheid, Sandra; Maffucci, Fulvio; Abella, Elena; Bradai, Mohamed Nejmeddine; Camedda, Andrea; Carreras, Carlos; Claro, Françoise; de Lucia, Giuseppe Andrea; Jribi, Imed; Mancusi, Cecilia; Marco, Adolfo; Marrone, Nicola; et al. (Global ecology and conservation, 2022)
Global warming is affecting habitat quality and availability on our planet and some species are predicted or are by now changing their distribution range. Here we show that loggerhead turtles have already started to expand their nesting range into the Western Mediterranean, which has until recently hosted only sporadic nests. We compiled information on nesting activity from beaches surrounding the Western Mediterranean and collected metadata on loggerhead turtle nests in Spain, France, Italy, and Tunisia between 2010 and 2020 to provide an exhaustive overview on the phenomenon of emerging new nest sites for loggerhead turtles. The number of recorded nests has increased drastically since 2013 from 1 to 3 nests/year to a record number of 84 registered in 2020. While this increase may partly be explained by grown awareness and reporting by citizens, there is no doubt of an upward trend in nesting activity. The nests are unevenly distributed over the study area with most nests occurring on the coasts of the warmer Tyrrhenian Sea. A hotspot analysis identified beaches in SW Italy, SE Sardinia, and NW Tunisia with statistically significant clustering of nests. Within these hotspots, three beaches in SW Italy and one in Tunisia had nests at least four out of the five last years. Nesting phenology corresponds to that of Eastern Mediterranean rookeries, and mean hatching success of naturally incubating, non-manipulated nests was 66 %, although there was variability across the region. Mean incubation durations also varied between countries indicating a diversity in inferred sex ratios, with sufficient female production to foster future colonisation of this region. Unfortunately, these beaches are already under high tourist pressure and subject to intense coastal development, imposing many threats to the females, eggs, and hatchlings. Thus, while this study reveals the unique opportunity to witness and study an ongoing new colonisation process in loggerhead turtles, it also calls for urgent proactive conservation actions to mitigate these threats and allow the turtles to establish new rookeries.